The Urgency of Applying Banking Prudential Principles in The Era of Disruption to Minimize Financing Risks - Sari, Anggi Puspita (Al-Muhasib: Journal of Islamic Accounting and Finance, 2023)
Market, liquidity, operational, and loan financing risks are common for banks. If the bank is unable to reclaim the primary credit it has extended or the money it is pursuing, financing risk will materialize. This kind of field study (field research) looks for and gathers data in areas where issues or phenomena arise of the application of the principle in muamalat financing, field research focuses on tracking down and examining already available materials in the field. The descriptive qualitative approach of data analysis is employed before being methodically assembled and analyzed. Using the 5C feasibility study in line with Law Number 21 of 2008 concerning Islamic Banking—Character, Capacity, Capital, Collateral, and Condition are fairly good—Bank Muamalat Indonesia is putting the Prudential Banking Principle into practice. Implementing repressive control of financing and taking action to resolve problematic financing by implementing 3R. Islamic banks must operate following Sharia principles, under the prudential concept stipulated in Article 2 of Law No. 7 of 1992, which governs Indonesian banking on the principles of economic democracy and prudence.